1984
DOI: 10.1037/0022-006x.52.3.480
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a multicomponent maintenance program on long-term weight loss.

Abstract: This study evaluated the effectiveness of a multicomponent program designed to enhance the maintenance of weight loss. Following a standard regimen of behavioral weight loss treatment, 43 moderately obese clients received either (a) six booster sessions or (b) six sessions of training in the use of a maintenance program consisting of self-help group meetings and client-therapist contacts by mail and telephone. The results of 15-and 21-month follow-up assessments revealed that the multicomponent program signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 1 publication
0
61
0
Order By: Relevance
“…There is considerable data demonstrating that individuals who are successful at losing and maintaining their weight have more communication with their researcher than those who lose contact. [17][18][19][20][21] It seems unlikely, however, that simply communicating electronically via e-mail over the Internet was the distinguishing feature because the use of the Internet has been found to be no more effective at maintaining weight than direct contact. 22 Finally, it is possible that the students used the information provided to them by the TMS as an early indicator of a small error in their energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable data demonstrating that individuals who are successful at losing and maintaining their weight have more communication with their researcher than those who lose contact. [17][18][19][20][21] It seems unlikely, however, that simply communicating electronically via e-mail over the Internet was the distinguishing feature because the use of the Internet has been found to be no more effective at maintaining weight than direct contact. 22 Finally, it is possible that the students used the information provided to them by the TMS as an early indicator of a small error in their energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, for example, 57% of dropouts indicated that slow weight loss was responsible for their withdrawal from treatment (Perri, McAdoo, Spevak, & Newlin, 1984). Likewise, a subsequent study found that women who dropped out during the first three months of treatment had achieved a significant lower weight loss than continuers (Wadden, Foster, Letizia, & Stunkard, 1992).…”
Section: Cognitive Factors and Attritionmentioning
confidence: 97%
“…On average, without continuing treatment, patients regain much of the weight they have lost within 2 or 3 years. A modest literature conducted by Jeffery and Wing (1999) among others has begun to explore different ways to improve on the long-term maintenance of weight loss (Perri, et al, 1984, 1988, 1989, 2001; Wing, et al, 1996, 1999, 2006; Jeffery, et al, 2003, 2004; Svetkey, et al, 1999, 2008). To date, however, most maintenance treatments reported in the research literature have failed to show continuing weight loss beyond 6 months of treatment.…”
Section: Introductionmentioning
confidence: 99%